1990
DOI: 10.1177/00220345900690s149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Topical Fluoride Preparations

Abstract: For practical reasons, evaluation of topical fluoride products must depend upon clinical and laboratory assessments. While not always a good predictor of clinical efficacy by itself, fluoride uptake is the most commonly used laboratory test. A consideration of the relationship between possible anticaries mechanisms of fluoride, different product types, and the meaning of various kinds of fluoride uptake data suggests that both the amount of fluoride taken up by early lesions and the amount of ambient fluoride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Fluoride uptake data have shown that amine fluoride (and APF) deposits more fluoride in enamel than NaF or SnF2 [Gron, 1977;Kirkegaard, 1977;Mellberg, 1990], ten Cate [1990] concluded that fluoride from depots in porous parts of the dentition and plaque may gradually redis solve . The results of this present study suggest that month ly applications of amine fluoride, even with a lower fluo ride concentration, ensure that enough fluoride is present for the direct or indirect interaction with the de-or remin eralization components of the caries process and thereby reduce its progression in the deciduous dentition.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride uptake data have shown that amine fluoride (and APF) deposits more fluoride in enamel than NaF or SnF2 [Gron, 1977;Kirkegaard, 1977;Mellberg, 1990], ten Cate [1990] concluded that fluoride from depots in porous parts of the dentition and plaque may gradually redis solve . The results of this present study suggest that month ly applications of amine fluoride, even with a lower fluo ride concentration, ensure that enough fluoride is present for the direct or indirect interaction with the de-or remin eralization components of the caries process and thereby reduce its progression in the deciduous dentition.…”
Section: Discussionmentioning
confidence: 99%
“…The posssibility that higher fluoride concentrations used at the same frequency might provide greater benefits should not be discounted. The additional benefits of daily rinsing as compared with weekly rinsing have not been demonstrat ed in controlled clinical studies, supporting the theory that the predominant action of fluoride is the remineralization of initial carious lesions [Arends and ten Cate, 1981;Mellberg. 1990].…”
Section: Frequency and Rational Use O F Fluoride Moutlirinsesmentioning
confidence: 95%
“…[19][20][21] Further, high fluoride uptakes did not necessarily show such a correlation, either. [21][22][23] Moreno et al 24 studied the solubility behaviour of hydroxyapatite at various levels of fluoride substitution. The maximum effect was obtained when only 50% of the hydroxyl groups had been replaced corresponding to the greatest lattice stability and reflecting a low lattice free energy (G).…”
Section: Introductionmentioning
confidence: 99%